Molecular evidence for multiple polyploidization and lineage recombination in the Chrysanthemum indicum polyploid complex (Asteraceae) - Yang, Wenhua (The New phytologist, 2006)
The Chrysanthemum indicum polyploid complex comprises morphologically differentiated diploids, tetraploids and hybrids between C. indicum and C. lavandulifolium. The relationships between species and cytotypes within this complex remain poorly understood. Random amplified polymorphic DNAs (RAPDs), intersimple sequence repeats (ISSRs) and chloroplast SSR markers were used to elucidate the genetic diversity and relationships of the C. indicum polyploid complex. Molecular analysis of three diploid and nine tetraploid populations provided strong evidence for recurrent origins and lineage recombination in the C. indicum polyploid complex. The high similarity in molecular marker profiles and cpDNA haplotypes between the diploids and tetraploids distributed in the Shen-Nong-Jia Mountain area of China suggested an autopolyploid origin of the tetraploids, while the tetraploids from other populations may have originated via allopolyploidization. Lineage recombination was revealed by the extensive sharing of chloroplast haplotypes and genetic markers among the tetraploid populations with different origins. Multiple differentiation and hybridization/polyploidization cycles have led to an evolutionary reticulation in the C. indicum polyploid complex, and resulted in the difficulties in systematic classification